Aplicativo mobile para divulgação de eventos - Dotti, Alexandre (2023)
This work presents the development of an application for the promotion and management of events. The proposal of this work was motivated by the growth of applications for mobile devices, especially for the Android operating system. As time goes by, the smartphone is increasingly present in the user's day to day life. It is a technology capable of simplifying and facilitating the lives of its owners, which has enabled developers to adapt and launch applications on the market with the aim of helping users in their daily tasks. The Central Student Directory of the Federal Technological University of Paraná has a certain lack of applications for event management. Based on this, a software was developed to manage and promote events, contributing to the control of tasks and the interaction of the community with the university routine. The project was implemented using the Java programming language, and the Google Firebase platform to store the application's data, control user authentication, present metrics about the application, measure user behavior, and send notifications. As a result, we have an application with the functionalities of registering events, registering for events, commenting and liking events, consulting events, registering newsletters, and consulting newsletters. For administrators, the application has the functionalities to query registered users by access profile, query areas that have more interest for users, and define the access profile of each user. A notification manager was also developed to alert users about the events scheduled for the day, preventing non-attendance.